An Effective Model for Improving Global Health Nursing Competence - Kang, Sun-Joo (Frontiers in Public Health, 2016)
This paper developed an effective model for improving global health nursing competence among undergraduate students. A descriptive case study was conducted by implementing four programs. All programs were conducted with students majoring nursing and healthcare, where the researcher was a program director, professor, or facilitator. These programs were analyzed in terms of students’ needs assessment, program design, and implementation and evaluation factors. The concept and composition of global nursing competence, identified within previous studies, were deemed appropriate in all of our programs. Program composition varied from curricular to extracurricular domains. During the implementation phase, most of the programs included non-Korean students to improve cultural diversity and overcome language barriers. Qualitative and quantitative surveys were conducted to assess program efficacy. Data triangulation from students’ reflective journals was examined. Additionally, students’ awareness regarding changes within global health nursing, improved critical thinking, cultural understanding, and global leadership skills were investigated pre and post-program implementation. We discuss how identifying students’ needs regarding global nursing competence when developing appropriate curricula.